2016
DOI: 10.17051/io.2016.54792
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Matematik Dersi Öğretim Programı Kazanımlarının TIMSS Bilişsel Alanlarına Göre Değerlendirilmesi

Abstract: ÖZ. Bu araştırmanın amacı, ortaokul matematik dersi öğretim programındaki kazanımlarının bilişsel niteliklerini sınıf düzeyinde ve öğrenme alanları ekseninde analiz etmektir. Çalışma doküman analizi olarak gerçekleştirilmiş olup, 2013 yılında Talim Terbiye Kurulunca yayımlanan ortaokul (5, 6, 7, 8) matematik dersi öğretim programı, TIMSS 2015 matematik çerçevesinde ifade edilen bilişsel alanlar ve alt boyutlar dâhilinde analiz edilmiştir. Araştırma bulgularına göre müfredat kazanımlarının bilişsel özellikleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
(7 reference statements)
0
11
0
5
Order By: Relevance
“…In their study, they stated that 30% of objectives of the 8 th -grade level was in the knowledge, 35% in the application and 35% in the reasoning domain. Although the rate of objectives about the reasoning domain in the mathematics curriculum was high, it is seen in studies (Başol, 2016;İncikabı, 2016) in the literature that this rate is low in mathematics questions of the entrance exams to secondary education institutions (PE and TPESE).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In their study, they stated that 30% of objectives of the 8 th -grade level was in the knowledge, 35% in the application and 35% in the reasoning domain. Although the rate of objectives about the reasoning domain in the mathematics curriculum was high, it is seen in studies (Başol, 2016;İncikabı, 2016) in the literature that this rate is low in mathematics questions of the entrance exams to secondary education institutions (PE and TPESE).…”
Section: Resultsmentioning
confidence: 98%
“…This shows the need to increase the number of questions requiring high-level cognitive skills during the central exams in our country, Turkey. İncikabı, Mercimek, Ayanoğlu, Aliustaoğlu and Tekin (2016) evaluated the objectives of the secondary school mathematics curriculum published in 2013 according to the TIMSS cognitive domains. In their study, they stated that 30% of objectives of the 8 th -grade level was in the knowledge, 35% in the application and 35% in the reasoning domain.…”
Section: Resultsmentioning
confidence: 99%
“…It can be said that the studies on textbooks and curricula in the context of TIMSS components emphasize certain points. It was observed that the studies examining the curricula largely focused on the 2009 and 2013 middle school and 2018 primary school mathematics curricula (Delil, Özcan & Işlak, 2020;İncikabı, Mercimek, Ayanoğlu, Aliustaoğlu & Tekin, 2016;Kılıç, Aslan-Tutak & Ertaş, 2014). İncikabı et al (2016) examined the cognitive qualities of the objectives in the middle school mathematics curriculum according to the cognitive domains expressed in the TIMSS 2015 mathematics framework.…”
Section: Introductionmentioning
confidence: 99%
“…Countries trying to keep up with the age with innovative educational approaches care about international exams (Biber et al, 2018). For this reason, countries carry out their own national exam activities and evaluate their rankings by participating in international exams (Çelen et al, 2011;Kumandaş & Kutlu, 2014 (Berberoğlu & Kalender, 2005;İncikabı et al, 2016). PISA is a test focused on creative thinking, access to information, using knowledge, discovering reading and writing skills (Schleicher, 2007).…”
Section: Extended Abstract 1 Introductionmentioning
confidence: 99%